Micromachining in Powder-Mixed Micro Electrical Discharge Machining - Gunawan Setia Prihandana; Muslim Mahardika; Tutik Sriani (Applied Sciences, 2020)
Micromachining in the micro-electric discharge machining (μ-EDM) process requires high material-removal rate with good surface quality. Power-mixed μ-EDM, a modified machining process by introducing specific powder into the dielectric fluid, is among the key inventions to achieving these requirements. This article presents a review of the implementation of powder-mixed micro-EDM processes for microfabrication. Special attention was given to the influence of the powder characteristics, such as the concentration, electrical conductivity, shape and size of the powder. Subsequently, when describing the use of powder for obtaining a high material-removal rate and surface quality, other major applications in μ-EDM for surface modification and geometrical accuracy were also discussed. Finally, some of the varied methods that are used in powder-mixed μ-EDM and industrialization challenges are extensively elaborated.